أثر تمكين المورد البشري على سلوك المواطنة التنظيمية - دراسة حالة المؤسسة العمومية للصحة الجوارية بولاية الأغواط - - قريشي, الزهرة; ديدوني, يوسف (جامعة الوادي - University of Eloued, 2022)
The study aimed to know the impact of empowering human resources (medical and paramedical staff) on the behavior of organizational citizenship in the public health institution in Laghouat?, The study started from a general question: What is the impact of empowerment on organizational citizenship behavior in the public health institution in the state of Laghouat? , A general hypothesis and a set of sub-hypotheses related to the dimensions of empowerment and its impact on organizational citizenship behavior have been formulated The researchers followed the descriptive approach by addressing the theoretical side as well as the practical side, and they used the questionnaire as a tool for the study containing 36 phrases, 85 forms were distributed, all valid for the study. The researchers also used the spss-22 program to analyze simple linear regression. It was concluded that there is a statistically significant effect at the significance level (α = 0.05) for all dimensions of empowerment on organizational citizenship behavior, and the leadership dimension is considered the least influential dimension on organizational citizenship behavior in the institution under study.
The impact of human resource empowerment on the organizational citizenship behavior -Case study atPublic Institutions for neighborhoodhealth in Laghouat
مقال
Keywords: التمكين , المورد البشري , القيادة , تفويض السلطة , الإتصال ,المواطنة التنظيمية